Spezialisierungsformen einer marktorientierten Landwirtschaft in Norwegen. Gezeigt an Beispielen aus Mittel-Jaeren - Gläßer, Ewald (ERDKUNDE, 1980)
The specialised and market-oriented agriculture of the Jaeren Plain south of Stavanger is analysed in two separate cases, those of the Njaerheim and Naerland settlements (gardar) with the method applied involving agricultural geographical as well as agricultural-economic criteria. As for source material the investigation is based chiefly on data collected by the author in 1979, which permits the development of the respective forms of land use and cattle keeping as well as resulting farming systems. The interpretation also considers, amongst others, the agrarian-social aspects, Dairy cattle keeping based on fodder cultivation appears to be the absolutely dominant factor. In several cases pig breeding and/or fattening are supplementary activities. Some small farms are characterised by special cultures (green houses) in the form of tomato cultivation as their chief activity. On the whole family farms as fulltime activities are predominant in central and south Jaeren, the majority of which are highly efficient dairy cattle farms combined with different supplementary lines in addition. The average net income of such a family farm is ahead of that of all Norwegian agricultural regions. Besides these agricultural geographical and agricultural-economic facts, forms of finishing and marketing agricultural products also play their role. Today the level land around Jaeren as one of the core regions of Norway’s agricultural production is marked increasingly by territorial controversies as a result of the rapidly progressing urban-industrial development, especially in the Stavanger-Sandnes region. Spatial planning concepts ought in any case to proceed from the assumption that at least in central and south Jaeren these territorial conflicts are resolved in favour of agriculture.